Pendampingan dan Pelatihan Strategi Pengelolaan Bisnis di Kawasan Wisata Muaro Jambi Di Desa Muara Jambi Kecamatan Maro Sebo Kabupaten Muaro Jambi - Dessy Elliyana; Fitriaty Fitriaty; Tona Aurora Lubis; Zulfina Adriani; Fitri Widiastuti (Jurnal Pengabdian Masyarakat Madani, 2021)
Creative economy entrepreneurs and the community around this tourist destination should be a concern for many parties, their readiness in dealing with changes that occur mus be balanced with the knowledge and strategies they must have in order to make it potential to be able to improve their standard of living and independence in entrepreneurship. The increase in creative economy business actors, they can provide employment opportunities for themselves and their surroundings so that the development of the tourism sector can go hand in hand with the development of the creative economy of the surrounding community. Assistance in developing business strategies is currently an important requirement for the Muara Jambi village community to be able to compete with other private and large entrepreneurs, so that they also have benefit from the development of these tourist destinations. The achievement target of  this activity is a change in mindset so that their business is more business-oriented with accsess to online-based sales. The Result from this activity are small business traders and local residents who are very enthusiastic and understanding of the material that has been provided is expected to be realized soon to increase family income.